(untitled) (Research, Society and Development, 2020)
Epistemology and the publication of records correlated to chemistry teaching are interesting and necessary themes for the formation of chemistry graduates. The work that gave rise to this article resulted from activities developed in the discipline of Teaching Internship of the Doctorate at REAMEC, being, however, a bibliographic and descriptive research, carried out on the Google Academic Platform. We reflect on the context of teaching and learning Chemistry, emphasizing the epistemological making of the chemistry teacher. Teaching requires thinking, reflecting, analyzing, commitment, motivation, knowledge of curriculum content. For this, it is necessary, a thought open and receptive to new perspectives on science, so that there are real changes and true constructions of knowledge, starting from the positioning of professors trainers in universities, with respect to the Theory of Knowledge, who experience in their teaching practices to the graduate and their epistemological form expressed in the act of teaching and learning continuously, about such Science. We conclude that the construction of knowledge happens from information considered as true, making, therefore necessary, a professional teacher, knowledgeable of the types of epistemological conceptions of Science, which permeate the eyes of students in initial formation, of the Degree course in Chemistry.